Quality of life in the management of small vestibular schwannomas: Observation, radiotherapy and microsurgery. (23rd August 2018) - Deberge, Sarah; Meyer, Anais; Le Pabic, Estelle; Peigne, Lucie; Morandi, Xavier; Godey, Benoit
Abstract : Objective: The aim of this study was to compare quality of life (QOL) in small unilateral vestibular schwannoma (VS) patients managed by microsurgery, radiotherapy or observation. Study design: A retrospective chart review. Methods: The study included a total of 142 patients with VS stage 1 or 2 according to the Koos classification and treated between January 2004 and December 2015. Microsurgery, radiotherapy and observation groups comprised 43, 46 and 53 patients, respectively. All patients completed four QOL (questionnaires: Short‐Form Health Survey 36, Hearing Handicap Inventory, Tinnitus Handicap Inventory and Dizziness Handicap Inventory Short‐Form). Clinical symptoms and QOL were compared among groups. Results: The average time interval between management and filling in the questionnaires was 66 months. There was no difference in QOL between the three groups on any of the four questionnaires. The most debilitating symptom was vertigo for all three groups. Tinnitus was a pejorative factor in the surgery group. Hearing level was deteriorated after microsurgery but there was no significant difference between the radiotherapy group and the middle fossa approach. Conclusion: Patients with small VS stage 1 and 2 had similar QOL, irrespective of management by observation, radiotherapy or microsurgery. The overall predictor for long‐term reduced QOL was vertigo. Vestibular rehabilitation could improve QOL in symptomatic patients.